Susceptibility loci for metabolic syndrome and metabolic components identified in Han Chinese: a multi‐stage genome‐wide association study. Issue 6 (30th March 2017) - Zhu, Yimin; Zhang, Dandan; Zhou, Dan; Li, Zhenli; Li, Zhiqiang; Fang, Le; Yang, Min; Shan, Zhongyan; Li, Hong; Chen, Jianhua; Zhou, Xianghai; Ye, Wei; et al.
Abstract: Metabolic syndrome (MetS), a cluster of metabolic disturbances that increase the risk for cardiovascular disease and diabetes, was because of genetic susceptibility and environmental risk factors. To identify the genetic variants associated with MetS and metabolic components, we conducted a genome‐wide association study followed by replications in totally 12, 720 participants from the north, north‐eastern and eastern China. In combined analyses, independent of the top known signal at rs651821 on APOA5, we newly identified a secondary triglyceride‐associated signal at rs180326 on BUD13 ( P combined = 2.4 × 10 −8 ). Notably, by an integrated analysis of the genotypes and the serum levels of APOA5, BUD13 and triglyceride, we observed that BUD13 was another potential mediator, besides APOA5, of the association between rs651821 and serum triglyceride. rs671 ( ALDH2 ), an east Asian‐specific common variant, was found to be associated with MetS ( P combined = 9.7 × 10 −22 ) in Han Chinese. The effects of rs671 on metabolic components were more prominent in drinkers than in non‐drinkers. The replicated loci provided information on the genetic basis and mechanisms of MetS and metabolic components in Han Chinese.